An Empirical Analysis of the Stochastic Behaviour of Short-Term Interest Rates in Singapore - TSE, Yiu Kuen (Institutional Knowledge at Singapore Management University, 1998)
This paper examines the stochastic behaviour of short-term interest rates in Singapore. We consider the following models of interest-rate structure: the lognormal model, the stable Paretian model and the mean-reversion model. Data on the three-month interbank rates are analysed. The mean-reversion model with conditional heteroscedasticity appears to fit the data adequately. [ABSTRACT FROM AUTHOR]